Multigenerational mobility in India - Anustup Kundu; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Most studies of intergenerational mobility focus on adjacent generations, and there is limited knowledge about multigenerational mobility-that is, status transmission across three generations. We examine multigenerational educational and occupational mobility in India, using a nationally representative data set, the Indian Human Development Survey, which contains information about education and occupation for three generations. We find that mobility has increased over generations for education, but not for occupation. We also find that there are stark differences across social groups, with individuals belonging to socially disadvantaged communities in India lagging behind in social progress. Multigenerational mobility for Muslims in education and occupation have decreased in comparison to Hindus over the three generations. While we find that there is an increase in educational mobility for other disadvantaged groups such as Scheduled Castes, Scheduled Tribes, and Other Backward Classes compared to General Castes, we do not find evidence of increased occupational mobility over the three generations.
Keywords: J15; J62; O12; 330; multigenerational mobility; occupational mobility; educational mobility; India